Pengaruh ukuran perusahaan, capital intensity dan sales growth terhadap penghindaran pajak - Pravitasari, Helga Ayu; Khoiriawati, Novi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of firm size, capital intensity and sales growth on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2016-2020. This research is a quantitative research that uses the associative type with a secondary method in the form of data on the annual financial statements of mining companies with sampling through www.idx.co.id . The sampling technique used purposive sampling method, so that obtained a sample of 132 data. This research is multiple linear regression analysis using SPSS. The result show that the first hypothesis is that firm size has no effect in tax avoidance. The second hypothesis is that capital intensity has no effect in tax avoidance. The third hypothesis is that sales growth has an effect on tax avoidance. Then, simultaneously firm size capital intensity and sales growth have on effect on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2016-2020.